Om å vandre i Kristiania og Oslo. Byen i Knut Hamsuns Sult (1890) og Jan Kjærstads Rand (1990) - Tunkiel, Katarzyna (Folia Scandinavica Posnaniensia, 2010)
The purpose of the paper is to compare the images of Oslo, formerly Kristiania, in two Norwegian novels, Hunger (1890) by Knut Hamsun and Rand (Brink, 1990) by Jan Kjærstad. The analysis is based on the fact that the main characters in both works wander around the Norwegian capital. Following problems are discussed in the paper: the protagonists’ relation to the city and the other, their alienation and similarity with the classical figure of the flâneur. The topography of the city in both novels and the role it plays for the main characters is also shortly described.